Presplit Blasting Technique in Treating Hard Overlying Strata: From Numerical Simulation to Field Practice - Baisheng Zhang; Zhiping Yang; Xuming Yang; Shuai Zhang (Advances in Civil Engineering)
The potential dynamic risk of the mined underground space with hard overlying strata is one of the main concerns for coal operators. This paper presents a comprehensive study on treating the hard overlying strata upon the coal seam through the presplit blasting technique. The properties of the overlying strata were firstly investigated and evaluated via the laboratory tests and theoretical analysis. With the consideration of the geological and mining condition of the research area, the critical parameters of the presplit blasting technique (e.g., unsaturation coefficient, borehole spacing, and the slit width) were consequently determined via the numerical simulation with the application of LS-DYNA. Then, the field practice in accordance with the determined parameters was carried out in Yuwu coal mine. The effectiveness of the presplit blasting technique was well verified when the microstructures of the surrounding rock were investigated. The success presented in this paper does not only demonstrate the feasibility of using the presplit blasting technique in treating the hard strata of underground mines but also provide a guideline in determining the critical parameters by the numerical simulation and theoretical analysis from the design aspect.